Annotated checklist of family- and genus-group names associated with Scoliidae (Hymenoptera, Aculeata) - Christopher K. Taylor (Journal of Hymenoptera Research, 2024)
Thirty-two family-group names and 161 genus-group names are listed for Scoliidae, including two fossil subfamilies and eight fossil genera, together with identification of type species and critiques of publication history. Campsomerinae was first made available in 1912. Contrary to previous usage, Argaman must be recognised as author of Bellimeris, Catharinimeris (not Cathimeris), Colpacampsomeris, Fasciomeris (not Fascimeris), Garantimeris, Lindenimeris, Phaleromeris (not Phalerimeris), Tetrasciton and Tristomeris. Tristomeris takes precedence as correct spelling over Tristimeris. A summary classification to genus level is provided for Scoliidae. Trielidina stat. nov. is recognised as a subtribe of Campsomerini.